2008
DOI: 10.1242/dev.015453
|View full text |Cite
|
Sign up to set email alerts
|

Deriving multipotent stem cells from mouse spermatogonial stem cells: a new tool for developmental and clinical research

Abstract: In recent years, embryonic stem (ES) cell-like cells have been obtained from cultured mouse spermatogonial stem cells (SSCs). These advances have shown that SSCs can transition from being the stem cell-producing cells of spermatogenesis to being multipotent cells that can differentiate into derivatives of all three germ layers. As such, they offer new possibilities for studying the mechanisms that regulate stem cell differentiation. The extension of these findings to human SSCs offers a route to obtaining pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 29 publications
(62 reference statements)
0
31
0
Order By: Relevance
“…New research has shown the derivation of pluripotent stem cells from neonatal and adult mouse testis that can differentiate to all cell types (Guan et al 2007;Nayernia 2007). These studies prove that ES-like cells were generated without genetic manipulation but under specific culture conditions (De Rooij and Mizrak 2008).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…New research has shown the derivation of pluripotent stem cells from neonatal and adult mouse testis that can differentiate to all cell types (Guan et al 2007;Nayernia 2007). These studies prove that ES-like cells were generated without genetic manipulation but under specific culture conditions (De Rooij and Mizrak 2008).…”
Section: Discussionmentioning
confidence: 64%
“…Our results showed that ES-like cells derived from spermatogonial stem cells share many molecular and cellular characteristics with embryonic stem cells; on cellular level, these cells have the same morphology with the sharp edge and can form embryoid body structure after transfer to bacteriological plate (De Rooij and Mizrak 2008).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In the testis, a subset of spermatogonial stem cells that abut the basement membrane of the seminiferous tubules in close proximity to supporting Sertoli cells can either self-renew or undergo 9 to 10 further divisions leading to clones of increased size (25). The spermatocytes that arise from these amplified spermatogonia then leave the basement membrane and enter the lumina of the tubules, where meiotic divisions and maturation to sperm are completed.…”
Section: Discussionmentioning
confidence: 99%
“…Pluripotent stem cells so far considered for regenerative medicine strategies include inner cell mass derived ES cells [53,54] , somatic derived induced pluripotent stem cells (iPS cells) [55] , fetal derived embryonic germ (EG) cells [56] and SSC derived multipotent germ stem (mGS) cells [57,58] . All of these cells form teratomas when injected to seminiferous tubules or subcutaneous tissue of immunocompromised mice and contribute to chimera formation when injected to a blastocyst.…”
Section: Ssc Pluripotencymentioning
confidence: 99%